Serum Gamma-Glutamyltransferase Levels Predict the Development of Cerebral Infarction in the Korean Population - Lee SM (Dove Medical Press, 2021)
Sang Min Lee,1 Eunhee Ha,2 Jae-Hong Ryoo3 1Department of Psychiatry, Kyung Hee University Medical Center, Kyung Hee University School of Medicine, Seoul, Korea; 2Department of Occupational and Environment Medicine, College of Medicine, Ewha Womans University, Seoul, Korea; 3Department of Occupational and Environmental Medicine, School of Medicine, Kyung Hee University, Seoul, KoreaCorrespondence: Jae-Hong RyooDepartments of Occupational and Environmental Medicine, School of Medicine, Kyung Hee University, 23 Kyungheedae-ro, Dongdaemun-gu, Seoul, 02447, KoreaTel +82-10-6235-2208Fax +82-2-969-0792Email armani131@naver.comPurpose: This study examined the relationship between serum gamma-glutamyltransferase concentration and the risk of cerebral infarction in the Koreans.Materials and Methods: A total of 209,481 out of 223,551 participants in the National Health Information Database who received medical checkups in 2009 were included in the final analysis. The diagnosis code ICD I63 was used for identifying cerebral infarction cases and tracked the development of cerebral infarction by 2013. Cox proportional hazards model was used to calculate hazard ratios (HRs) for cerebral infarction and their confidence interval (CI).Results: During a follow-up period of 915,387.5 person-years, 2403 incident cases of cerebral infarction developed between 2009 and 2013. After adjusting for multiple covariates, the hazard ratios (95% confidence interval) for incident cerebral infarction, comparing the second, third, and fourth quartile of serum gamma-glutamyltransferase levels with the first quartile, were 1.11 (0.98– 1.27), 1.39 (1.22– 1.58), and 1.49 (1.29– 1.71), respectively (P for trend < 0.001).Conclusion: Elevated serum gamma-glutamyltransferase levels were independently associated with the future development of cerebral infarction in Koreans.Keywords: gamma-glutamyltransferase, cerebral infarction, stroke